Beyond platitudes: a qualitative study of Australian Aboriginal people's perspectives on biobanking. Issue 9 (19th September 2021) - Hermes, Azure; Wiersma, Miriam; Kerridge, Ian; Easteal, Simon; Light, Edwina; Dive, Lisa; Lipworth, Wendy
Abstract: Background: Biobanks are vital resources for genetics and genomics, and it is broadly recognised that for maximal benefit it is essential that they include samples and data from diverse ancestral groups. The inclusion of First Nations people, in particular, is important to prevent biobanking research from exacerbating existing health inequities, and to ensure that these communities share in the benefits arising from research. Aims: To explore the perspectives of Australian Aboriginal people whose tissue – or that of their family members – has been stored in the biobank of the National Centre for Indigenous Genomics (NCIG). Methods: Semi‐structured interviews with 42 Aboriginal people from the Titjikala, Galiwinku, Tiwi Islands, Yarrabah, Fitzroy Crossing, Derby, One Arm Point and Mulan communities, as well as a formal discussion with A. Hermes, an Indigenous Community Engagement Coordinator at the NCIG who had conducted the interviews. The interviews and the structured discussion were double coded using a procedure informed by Charmaz's outline of grounded theory analysis and Morse's outline of the cognitive basis of qualitative research. Results: In this article, we report on A. Hermes' interviews with members from the above Aboriginal communities, as well as on her personal views, experiences, and interpretations of the interviews she conducted with other community members. We found that participation in the NCIG biobank raised issues around broken trust, grief and loss, but also – somewhat unexpectedly – was perceived as a source of empowerment, hope and reconnection. Conclusions: This research reminds us (again) of the need to engage deeply with communities in order to respond appropriately with respect for their cultural values and norms, and to develop culturally relevant policies and processes that enhance the benefits of biobank participation and minimise potential harms.